Integrated Analysis of Glutathione Metabolic Pathway in Pancreatic Cancer - Wu, Xingui; Yu, Ruyuan; Yang, Meisongzhu; Hu, Yameng; Tang, Miaoling; Zhang, Shuxia; Abudourousuli, Ainiwaerjiang; Li, Xincheng; Li, Ziwen; Liao, Xinyi; Xu, Yingru; Li, Man; et al. (Frontiers in Cell and Developmental Biology, 2022)
Metabolic enzymes (MEs) play critical roles in various types of cancer. However, MEs have not been systematically and thoroughly studied in pancreatic cancer (PC). Global analysis of MEs in PC will help us to understand PC progressing and provide new insights into PC therapy. In this study, we systematically analyzed RNA sequencing data from The Cancer Genome Atlas (TCGA) (n = 180+4) and GSE15471 (n = 36 + 36) and discovered that metabolic pathways are activated in PC. Co-expression network modules of MEs were constructed using weighted gene co-expression network analysis (WGCNA), which identified two key modules. Both modules revealed that the glutathione signaling pathway is activated in PC and correlated with pancreatic cancer stages. Notably, Glutathione peroxidase 2 (GPX2), an important gene involved in glutathione signaling pathway, is a hub gene of the key modules. Analysis of immune microenvironment components reveals that pancreatic cancer stage is associated with M2 macrophages, the marker gene of which is significantly correlated with GPX2. The results indicated that GPX2 promotes pancreatic cancer progression, providing new insights for future targeted therapy.